Tingkat Kepuasan Pasien Rawat Jalan Terhadap Mutu Pelayanan Kesehatan di Puskesmas Sendana - Zulfahmidah Zulfahmidah; Resky Asfiani Rahman (Yayasan Citra Cendekia Celebes, 2021)
Background and Objectives: Patient satisfaction is an indicator indicator of providing health services to the community. One of the development efforts in the health sector is the availability of quality health services such as the existence of a health center. Puskesmas must have good quality health services that can be seen from the performance or the perceived benefits, in order to give satisfaction to patients. The purpose of this study was to see the level of outpatient satisfaction with health services, so that it can be used as evaluation material for the health center. Methods: This study used a quantitative descriptive research method with a cross-sectional study design. The research variables included the quality of health services which consisted of aspects of reliability, responsiveness, empathy, facilities, and assurance. The population in this study were patients who visited the Sendana Health Center. The sampling technique was accidental sampling and obtained 31 respondents. Results: The results of the study the patient scores were analyzed and grouped according to their level in order to obtain a satisfaction level of 70.4% reliability aspects, 67.5% responsiveness, 66.9% empathy, 57.7% facilities, and 65.3% assurance. Conclusion: Overall satisfaction level is included in the satisfied category.